2013
DOI: 10.1159/000350829
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Pituitary Imaging Abnormalities and Clinical and Biochemical Phenotypes in Children with Congenital Growth Hormone Deficiency: Data from an International Observational Study

Abstract: Background/Aims: Magnetic resonance imaging (MRI) is used to investigate the etiology of growth hormone deficiency (GHD). This study examined relationships between MRI findings and clinical/hormonal phenotypes in children with GHD in the observational Genetics and Neuroendocrinology of Short Stature International Study, GeNeSIS. Methods: Clinical presentation, hormonal status and first-year GH response were compared between patients with pituitary imaging abnormalities (n = 1,071), patients with mutations in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 37 publications
4
45
2
2
Order By: Relevance
“…Slightly more than one-third of our analysed study population was girls. Similar gender proportions have been reported previously in GeNeSIS (12) and in other studies (24,25). This gender disparity has been attributed to ascertainment or referral bias, as short stature may be socially more detrimental to boys.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Slightly more than one-third of our analysed study population was girls. Similar gender proportions have been reported previously in GeNeSIS (12) and in other studies (24,25). This gender disparity has been attributed to ascertainment or referral bias, as short stature may be socially more detrimental to boys.…”
Section: Discussionsupporting
confidence: 86%
“…As described in a previous analysis of the GeNeSIS database (12) and other studies, patients with hypothalamic-pituitary genetic defects (13,14,15,16) or anatomical abnormalities of the hypothalamic-pituitary region (17,18,19) had more severe GHD and were more frequently diagnosed as MPHD. In our 4-year follow-up cohort seven of 22 patients with hypothalamic-pituitary genetic defects progressed to MPHD (32%), predominantly those with PROP1 mutations, but also two patients with GH1 mutation.…”
Section: Discussionmentioning
confidence: 64%
“…12-14 among auxiliary diagnostics methods, MRi has been gaining an apparent role as an indicator of hormonal deficiencies of the pituitary. 4,5,[15][16][17] according to the guidelines of several endocrine societies, GH stimulation tests are not necessary in the event of co-existence of clinical signs of GHD and structural anomalies of the hypothalamic-pituitary area in the MRi. 2 Pituitary stalk interruption syndrome with ectopia of the posterior pituitary (PSiS), characterized by the hyperintensive T1 signal, is one of the typical qualitative alternations in the MRi related to GHD.…”
Section: Discussionmentioning
confidence: 99%
“…4,17,19 according to Coutant et al, children with GHD and abnormal MRi manifest greater height deficit and younger chronological age at initial diagnosis. 4 Moreover, Maghnie et al found bone age to be more delayed in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation